Development Model for Creative Economy Based on Local Wisdom: The Case of Songkok Recca in South Sulawesi Province - Akhmad; Amir; Buyung Romadhoni; Anwar Hafid; Muhammad Al-khahfi Akhmad, (International Journal of Scientific Research and Management (IJSRM), 2025)
This research analyzes the potential development of a creative economy based on local wisdom through a case study ofsongkok recca craftsmanship in Awangpone District, Bone Regency, South Sulawesi. Using a qualitative-descriptive approach, the study identifies production structures, traditional marketing patterns, and sustainability challenges within this craft industry. Through comprehensive SWOT analysis, a quadruple helix-based development model is formulated that integrates the roles of government, academia, business actors, and communities within the creative economy ecosystem. The findings indicate that digital transformation, preservation of traditional knowledge, raw material conservation programs, and quality standardization based on geographical indications are key components in the development strategy. This model demonstrates how local wisdom values can be integrated into a contemporary creative economy framework to create sustainable enterprises that maintain cultural identity while remaining responsive to global market dynamics.